INOVASI PELAYANAN PUBLIK BERBASIS CHATBOT WHATSAPP ‘MOJOKERTO EXCELENT COURT’ (MOXER) DI PENGADILAN NEGERI MOJOKERTO KELAS 1A KABUPATEN MOJOKERTO - Yusuf Ibrahim, Akmal; Isbandono , Prasetyo (Universitas Negeri Surabaya, 2023)
The term e-Government in Indonesia only started in early 2000. Each bureaucracy certainly has its own innovations in improving service quality and running E-Government. One of the innovations that researchers took for the case study was an innovation created by the Mojokerto District Court under the name MOXER (Mojokerto Excellent Court). The research uses a descriptive qualitative method approach. Data sources include primary data and secondary data, data collection techniques include observation, interviews, documentation. Data analysis was carried out by data collection, data reduction, data presentation stages, and drawing conclusions. The research results of Minister of PAN & RB Regulation No. 91 of 2021 concerning the Development of Public Service Innovation explain the criteria for public service innovation as follows: (1) Having novelty, it is considered appropriate because the innovation is created from a new idea or concept. (2) Effective, considered to be effective in improving employee performance and public services. (3) Useful, considered appropriate because during its implementation it still has benefits to employees and the community to this day. (4) Easy to spread, considered not to meet the indicators because the innovation is not optimal in its distribution and only a few people understand the innovation. (5) Sustainable, considered satisfactory because the MOXER innovation is still used by all employees and can still be accessed and developed for the community as well. The conclusion above regarding MOXER's public service innovation can be considered to be in accordance with these indicators, however there is an obstacle, namely the lack of socialization to the public so that only a few people know about this innovation. Keywords: E-Government, Public Services, Innovation